2021
DOI: 10.1007/s00572-020-01010-5
|View full text |Cite|
|
Sign up to set email alerts
|

High resilience of the mycorrhizal community to prescribed seasonal burnings in eastern Mediterranean woodlands

Abstract: Fire effects on ecosystems range from destruction of aboveground vegetation to direct and indirect effects on belowground microorganisms. Although variation in such effects is expected to be related to fire severity, another potentially important and poorly understood factor is the effects of fire seasonality on soil microorganisms. We carried out a large-scale field experiment examining the effects of spring versus autumn burns on the community composition of soil fungi in a typical Mediterranean woodland. Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…Instead, these fungi may be activated by temperature thresholds reached during high‐severity fires, which are common in chaparral and some Pinaceae forests (Agee, 1993; Keeley & Zedler, 2009; Neary et al, 1999). Specifically, our burned communities were dominated by Ascomycota in the genera Pyronema , Penicillium , and Aspergillus , similar to dominant post‐fire fungal species in Mediterranean shrublands (Livne‐Luzon et al, 2021), boreal spruce (Whitman et al, 2019), and montane pine forests (Bruns et al, 2020; Pulido‐Chavez et al, 2021). Both Pyronema ( P. omphalodes ) and Aspergillus ( A. fumigatus ) are known pyrophilous fungi of California chaparral (Dunn et al, 1982), and we identified additional species, including P. domesticum , A. udagawae , and A. elsenburgensis .…”
Section: Discussionmentioning
confidence: 63%
“…Instead, these fungi may be activated by temperature thresholds reached during high‐severity fires, which are common in chaparral and some Pinaceae forests (Agee, 1993; Keeley & Zedler, 2009; Neary et al, 1999). Specifically, our burned communities were dominated by Ascomycota in the genera Pyronema , Penicillium , and Aspergillus , similar to dominant post‐fire fungal species in Mediterranean shrublands (Livne‐Luzon et al, 2021), boreal spruce (Whitman et al, 2019), and montane pine forests (Bruns et al, 2020; Pulido‐Chavez et al, 2021). Both Pyronema ( P. omphalodes ) and Aspergillus ( A. fumigatus ) are known pyrophilous fungi of California chaparral (Dunn et al, 1982), and we identified additional species, including P. domesticum , A. udagawae , and A. elsenburgensis .…”
Section: Discussionmentioning
confidence: 63%
“…Instead, these fungi may be activated by temperature thresholds since this fire burned at high severity with ash depths up to 12cm, similar to fires in Pinaceae forests. Specifically, we found that our communities were dominated by Ascomycota in the genera Pyronema, Penicillium, and Aspergillus, which have been shown to dominate post-fire boreal spruce forests (Whitman et al, 2019), montane pine forests (Bruns et al, 2020), and Mediterranean ecosystems (Fujimura et al, 2005;Livne-Luzon et al, 2021;Whitman et al, 2019). Both Pyronema (P. omphalodes) and Aspergillus (A. fumigatus) are known as fireresponsive species in California chaparral (Dunn et al, 1982).…”
Section: Pyrophilous Fungi Dominate the Burned Communities And Drive Successionmentioning
confidence: 85%
“…Instead, these fungi may be activated by temperature thresholds reached during high severity fires, which are common in chaparral and some Pinaceae forests (Agee, 1993;Keeley & Zedler, 2009;Neary et al, 1999). Specifically, our burned communities were dominated by Ascomycota in the genera Pyronema, Penicillium, and Aspergillus, similar to dominant fungal species post-fire in Mediterranean shrublands (Livne-Luzon et al, 2021), boreal spruce (Whitman et al, 2019), and montane pine forests (Bruns et al, 2020;Fujimura et al, 2005;Pulido-Chavez et al, 2021). Both Pyronema (P. omphalodes) and Aspergillus (A. fumigatus) are known pyrophilous fungi of California chaparral (Dunn et al, 1982), and we identified additional species including P. domesticum, A. udagawae, and A. elsenburgensis.…”
Section: Pyrophilous Fungi Dominate the Burned Communitiesmentioning
confidence: 87%
“…Grassland soil and sand were used as potting material. The soil was collected in herbaceous Mediterranean grassland, lacking EM host plants - according to previous experiments (Livne◻Luzon et al ., 2017; Livne-Luzon et al ., 2021b) from a field near Tel-Hai College (N 35°34’47"E 58°33’14”). The potting material was mixed (50% sand, 50% grassland soil) using an electric cement mixer.…”
Section: Methodsmentioning
confidence: 99%